Sosialisasi Makanan Sehat, Bergizi dan Halal dalam Perspektif Islam di Rumah Tahanan Negara (Rutan) Kelas IIB Bengkayang Kanwil Kemenkumham Kalimantan Barat - Fathul Khair; Eka Ratna Dewi (Syntax Corporation Indonesia, 2024)
The socialization of healthy, nutritious, and halal food from an Islamic perspective was carried out at the Class IIB Bengkayang State Prison (RUTAN). This research aims to increase the understanding of the inmates about the importance of consuming food in accordance with Islamic teachings, both in terms of health and spirituality. This activity involved an interactive lecture and discussion method by presenting resource persons from the Office of the Ministry of Religion of Bengkayang Regency. The results show the high enthusiasm of the inmates, as seen from the active participation and interest in understanding the concept of halal food and its benefits. This activity succeeded in providing practical and spiritual knowledge about halal food as an effort to foster the morale and health of the inmates.